Avaliação da produção de etanol 2g, xilitol e biomassa celular em meios sintéticos e hidrolisados lignocelulósicos pela levedura Meyerozyma guilliermondii - Perna, Michelle dos Santos Cordeiro (Universidade Federal de São Carlos, 2023)
Lignocellulosic biomass is the second largest source of carbon available on the planet. However, the viability of biorefineries depends on overcoming challenges such as the search for microorganisms capable of converting pentoses into 2G ethanol and high added value products. Thus, the present work aimed to evaluate the production of 2G ethanol and xylitol by the yeast Meyerozyma guilliermondii (CCT7783) from residues from the production of pencils and sugarcane straw. The yeast M. guilliermondii was adapted on xylose and the exact results that the specific growth rate was 75% higher for spontaneously adapted strains. In the second phase of the study, the adapted strains were applied in a study of the effect of fermentation conditions and the required results that high hypoxic conditions and high rotations lead to a reduction in biomass production and an increase in xylitol production. Ethanol production was higher with increasing concentration of pentoses and inoculum. In the fermentation of the hydrolysates approximately 50% of the sugars were converted into 2G ethanol and 7% into xylitol for both considered hydrolysates, having a controlled effect on the fermentation time for the hydrolysates from pencil residues. The yeast M. guilliermondii has potential for application in biorefinery processes and optimized conditions can lead to a targeted biosynthesis with higher yields.
Evaluation of the production of second generation ethanol (2G), xylitol and cell biomass in synthetic media and lignocellulosic hydrolysates by the yeast Meyerozyma guilliermondii
Keywords: Etanol 2G; Xilitol; Levedura não convencional; Biomassa celular; Proteína microbiológica; Biorrefinaria; Biomassa lignocelulósica; Palha de cana-de-açúcar; Resíduos de madeira; Hidrolisados lignocelulósicos; Meyerozyma guilliermondii; Ethanol 2G; Xylitol; Unconventional yeast; Cellular biomass; Single cell protein; Biorefinary; Lignocellulosic biomass; Sugar cane straw; Wood waste; Lignocellulosic hydrolysates; CIENCIAS EXATAS E DA TERRA::QUIMICA